Instructionally Embedded Assessment: Theory of Action for an Innovative System - Clark, Amy K.; Karvonen, Meagan (Frontiers in Education, 2021)
Policy shifts in the United States are beginning to reduce the emphasis on using statewide assessment results primarily for accountability and teacher evaluation. Increasingly, there are calls for and interest in innovative and flexible assessments that shift the purposes of assessment and use of results toward instructional planning and student learning. Under the Innovative Assessment Demonstration Authority, some states are exploring options for replacing traditional large-scale summative assessments with innovative measures. However, many of these programs are still in early phases of planning and research and have not yet fully articulated how the innovative system achieves desired outcomes. This conceptual paper presents an argument in the form of a theory of action for a flexible and innovative assessment system already in operational use. The system replaces traditional summative assessments with large-scale through-year Instructionally Embedded assessments. We describe the components of the theory of action, detailing the theoretical model and supporting literature that illustrate how system design, delivery, and scoring contribute to the intended outcomes of teachers using assessment results to inform instruction and having higher expectations for student achievement, in addition to accountability uses. We share considerations for others developing innovative assessment systems to meet stakeholders’ needs.